Elite athletes' experiences of interpersonal violence in organized sport in Germany, the Netherlands, and Belgium. Issue 4 (3rd April 2021) - Ohlert, Jeannine; Vertommen, Tine; Rulofs, Bettina; Rau, Thea; Allroggen, Marc
Abstract: Interpersonal violence in sport occurs in different forms, from emotional abuse, overtraining, bullying, physical aggression and pressuring to punishment and sexual abuse. Due to the use of different definitions, a comparison of prevalence estimates between studies in different countries has not been possible to date. The aim of the current study was thus to present the prevalence estimates of interpersonal violence in elite sport for the Netherlands, Belgium (Flanders), and Germany and to examine the overlap of three types of interpersonal violence. Data from two different surveys (one in the Netherlands and Flanders and another in Germany) of a total of 1, 665 elite athletes ( n = 533 from the Netherlands and Flanders, n = 1, 132 from Germany) were used. Athletes were asked to answer questions about their experiences of psychological, physical, and sexual violence in the context of organized sport. In general, lifetime prevalence estimates for all three types of interpersonal violence are more than 24% in elite athletes, with the highest numbers for psychological violence. Compared to representative population samples the prevalence rate of psychological violence seems to be particularly high. Gender differences were only evident for sexual violence, with female athletes showing higher prevalence estimates than male athletes. Furthermore, a high overlap of experiences of the three different forms of interpersonal violence was found for all three countries. The differences in prevalence estimates between the three countries are discussed.